2000
DOI: 10.1021/jp992398v
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies Using X-ray Absorption Spectroscopy of Intermediates Formed by Reaction of Ozone with Halogeno(dodecaphenylporphyrinato)manganese(III) Derivatives

Abstract: Difference EXAFS and XANES studies at the Mn K-edge are reported which shed light on the mechanisms of activation of the title compounds by ozone. The reaction of ozone with either the chloro- or bromoporphyrinato Mn(III) derivatives yields the same intermediate in which the metal is in a formally tetravalent (IV) state. The coordination scheme includes the four equatorial pyrrolic nitrogen atoms of the porphyrin plus two ozone molecules arranged in a symmetrical configuration with respect to the porphyrin cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…In the manganese( V ) reference compound 3 the short manganese–nitrogen separation of the nitrido group was found at 1.51 Å, visible as a shoulder at 1.5 Å in the FT‐EXAFS spectrum at the Mn K‐edge (Figure 5 d). This value is in excellent agreement with those found for similar nitridomanganese( V ) complexes 14, 23a, 14, 29. Table 3 summarizes the structural parameters of the reaction products of 1 and 2 with 4‐PPNO ( 4 and 5 , respectively).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In the manganese( V ) reference compound 3 the short manganese–nitrogen separation of the nitrido group was found at 1.51 Å, visible as a shoulder at 1.5 Å in the FT‐EXAFS spectrum at the Mn K‐edge (Figure 5 d). This value is in excellent agreement with those found for similar nitridomanganese( V ) complexes 14, 23a, 14, 29. Table 3 summarizes the structural parameters of the reaction products of 1 and 2 with 4‐PPNO ( 4 and 5 , respectively).…”
Section: Resultssupporting
confidence: 86%
“…A fivefold coordination is also more probable as the additional backscatterer has a relatively short distance (≈1.8–1.9 Å). In an octahedral coordination the distance is expected to be longer 29. For example, for an octrahedral [(DPPF 20 )Mn IV (O 3 ) 2 ] complex, two MnO ozone bond lengths of 2.09 Å have been found.…”
Section: Resultsmentioning
confidence: 99%
“…A search for all organometallic (i.e., structures containing organic ligands bound to a metal atom) h 3 -ozone complexes returned only two studies describing organometallic complexes having a dihedral angle between the O 3 and O-metal-O planes less than 135 . 62,63 The rst was an experimental study of a Mn organometallic complex having a corresponding dihedral angle of 116 . 62 The second was a computational study of small metal complexes (e.g., O 3 Fe(CO) 3 and O 3 Ru(CO) 3 ).…”
Section: Structural Analysismentioning
confidence: 99%
“…10 EXAFS studies showed that the compound formed when [MnCl(por)] [por 22 = 5,10,15,20-tetrakis(pentafluorophenyl)decaphenylporphyrinate] is exposed to ozone has two O 3 molecules coordinated in unsymmetric bidentate mode. 11 Studies of the new substituted salpn complexes of Mn(IV) of the type [Mn 4 (salpn)O] 2 , and a comparison with literature magnetic and structural data, established that the antiferromagnetic coupling constant J increased in magnitude in approximately linear fashion with the MnOMn bridging angle. This led to the suggestion that the dioxygen-evolving complex (OEC) of Photosystem II (PS II) is more complex than has been supposed.…”
Section: Manganese In High Oxidation Statesmentioning
confidence: 93%